Literature Study: Acute Myeloid Leukimia (AML) - Pramesti, Evane Dyahayu; Dhevi, Ni Made Saithanya Gitanjali; Hudhori, Syalsa; Salsabila, Ericha Zabrina; Asriantin, Isna; Anggoro, Joko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Leukemia is a cancer that originates from cells that initially develop into blood cells. Leukemia can be classified as acute or chronic, depending on how quickly the disease appears and how it progresses in the body. This literature review aims to determine the treatment for patients with AML depending on the subtype. This literature review used journal review methods and data searches through various sources. The results of the literature study found that Acute Myeloid Leukemia (AML) is divided into six subtypes. AML is caused by clonal transformation of hematopoietic cells through chromosomal abnormalities and gene mutations, with risk factors including exposure to radiation, benzene, smoking, chemotherapy therapy, the development of chronic myeloid neoplasms, aging, and predisposing diseases. Diagnosis of AML involves peripheral blood and bone marrow analysis, immunophenotyping, cytogenetics, molecular cytogenetics, and imaging to detect the presence and characteristics of leukemic cells. Treatment of AML includes induction therapy, consolidation therapy, and response monitoring, with special considerations for the selection of chemotherapy regimens, stem cell transplantation, and transfusion support to manage associated complications. In conclusion, Acute Myeloid Leukemia (AML) is a condition in which myeloblasts undergo excessive proliferation and fail to differentiate into granulocytes. This condition causes the bone marrow to fill with myeloblasts.